Changes in small organic N during early stages of soil development. (July 2017) - Warren, Charles R.
Abstract: During the early stages of ecosystem development there are increases in plant and soil microbial biomass, nutrient availability and rates of nutrient cycling; but little is known about how pools of small organic N vary during the initial stages of soil development. The aim of this study was to examine how the pool of small organic N compounds varies during the initial stages of soil development, and if age differentially affects D- and L-enantiomers of protein amino acids. Measurements were made at a soil chronosequence on the east coast of Tasmania that comprised a series of sub-parallel beach dunes and ridges varying in age from <100 years to 5500 years. Capillary electrophoresis-mass spectrometry was used to identify and quantify the main small organic N compounds in free, adsorbed and microbial fractions of the soil; while chiral liquid chromatography-mass spectrometry was used to quantify amino acid enantiomers in hydrolysed soil and the free, adsorbed and microbial fractions of soil. CE-MS detected 66 small (<250 Da) organic N compounds of which 63 could be positively identified. Small organic N was dominated by protein amino acids, while there were also large amounts of quaternary ammonium compounds and alkylamines. There were differences among chronosequence sites in the profile of small organic N, but these differences were not monotonically related to age and there was no evidence for a build-up of recalcitrant compounds over time. Differences were instead site-specific and related to presence/absence of particular non-protein amino acids which probably related to the presence/absence of specific plants and/or microbes that produce and/or can metabolise different non-protein amino acids. In free solution and microbial biomass D enantiomers of many amino acids were below detection limits (i.e. < 0.125 nmol g −1 ) and D-enantiomers were at low concentrations relative to L enantiomers such that across all ages and replicates the summed concentration ofd -amino acids was 0-3-0.6% of L amino acids. There was no evidence that absolute or relative concentrations of D-enantiomers in free solution, microbial biomass or hydrolysates were larger at the older chronosequence sites. The consistent lack of an effect of soil age on D/L probably indicates that the turnover of soil proteins is comparatively rapid and thus soil proteins are similarly young even among sites in which soil age is vastly different. Highlights: We measured small organic N at chronosequence sites aged <100 years–5500 years. Small organic N differed among sites, but these differences were not monotonically related to age. d -amino acids in free solution and microbial biomass were 0-3-0.6% of L amino acids. d -amino acids were not more abundant at the older sites.